Epilepsy: a comprehensive textbook. - Engel Jr., Jerome; Pedley, Timothy A. (Lippincott Williams y Wilkins, 2008)
Written and edited by world-renowned authorities, this three-volume work is, to quote a reviewer, "the definitive textbook about seizures and epilepsy". This Second Edition is thoroughly updated and gives you a complete print and multimedia package: the three-volume set plus access to an integrated content Website.